A Systematic Review of Human Infections by Pseudomonas mendocina - Petros Ioannou; Georgios Vougiouklakis (Tropical Medicine and Infectious Disease, 2020)
Pseudomonas mendocina is a Gram-negative, rod-shaped, aerobic bacterium that belongs in the family Pseudomonadaceae and has been isolated from water and soil. Even though it is thought to cause infections quite rarely in humans, it can cause severe infections even in immunocompetent individuals. The aim of this study was to systemically review all cases of human infection by P. mendocina in the literature and describe their epidemiology, microbiology, antimicrobial susceptibility, treatment and outcomes. Thus, a systematic review of PubMed for studies providing epidemiological, clinical, microbiological as well as treatment data and outcomes of Pseudomonas mendocina infections was conducted. In total, 12 studies, containing data of 16 patients, were included. The commonest P. mendocina infections were infective endocarditis, central nervous system infections and skin and soft tissue infections (SSTIs). Fever was the main presenting symptom, while sepsis was evident in almost half the patients. Pseudomonas mendocina was susceptible to most antibiotics tested. Mortality was low in all different infection types. Third or fourth generation cephalosporins and quinolones are the commonest agents used for treatment, irrespectively of the infection site.